Identification of joint patterns during gait in children with cerebral palsy: a Delphi consensus study. (28th August 2015) - Nieuwenhuys, Angela; Õunpuu, Sylvia; Van Campenhout, Anja; Theologis, Tim; De Cat, Josse; Stout, Jean; Molenaers, Guy; De Laet, Tinne; Desloovere, Kaat
Abstract : Aim: This study aims to achieve an international expert consensus on joint patterns during gait for children with cerebral palsy (CP) by means of Delphi surveys. Method: In Stage 1, seven local experts drafted a preliminary proposal of kinematic patterns for each lower limb joint in the sagittal, coronal, and transverse plane. In Stage 2, 13 experts from eight gait laboratories (four in the USA and four in Europe), participated in a Delphi consensus study. Consensus was defined by a pre‐set cut‐off point of 75% agreement among participants. Results: After the first stage, 44 joint patterns were presented in a first survey and 29 patterns reached consensus. Consensus improved to 47 out of 48 patterns in the third survey. Only one pattern, 'abnormal knee pattern during loading response', did not reach consensus. The expert panel agreed to define six patterns for the knee during swing, most of them representing characteristics of a stiff knee pattern. Interpretation: The defined joint patterns can support clinical reasoning for children with CP as joint patterns during gait might be linked to different treatment approaches. Automating the classification process and incorporating additional trunk, foot, and electromyography features should be prioritized for the near future. What this paper adds: A new gait classification system for children with cerebral palsy. Expert consensus includes lower limb joint patterns across three anatomical planes. Alternative proposal for classification of stiff knee. This article is commented on by Chambers on page228 of this issue.